MICE Sebagai Instrumen Soft Power: Peran KTT ASEAN dalam Diplomasi Pariwisata Indonesia - Achlis Nur Fajar (Tamasya : Jurnal Pariwisata Indonesia, 2026)
MICE tourism (Meetings, Incentives, Conferences, Exhibitions) is a sub-sector with high economic value and a unique capacity to play a diplomatic role through interaction between international actors. At the regional level, the ASEAN (Association of Southeast Asian Nations) Summit (Summit) has been used by Indonesia not only for economic purposes, but also as an arena for public diplomacy and soft power development. This article examines how the ASEAN Summit (especially the series of ASEAN 2023 activities spread across several locations including Labuan Bajo, Yogyakarta, and Jakarta) shows the function of MICE as a soft power instrument in Indonesian tourism diplomacy. By combining a literature review on soft power and tourism diplomacy, an analysis of official documents, MICE industry reports, and a case study of the 2023 ASEAN Summit, this paper identifies the mechanisms of influence, determinants of effectiveness, economic and reputational impact, and policy challenges. The results show that the ASEAN Summit provides a great opportunity for nation branding and international public engagement, but its effectiveness depends on policy synergy, MICE infrastructure readiness, image management, and post-event strategies to turn temporary exposure into long-term benefits.